Contamination assessment, source apportionment and associated health risks of PTEs in agricultural soil under five land-use patterns in Sanya, China - Jian-zhou Yang; Yan-gang Fu; Qiu-li Gong; Sheng-ming Ma; Jing-jing Gong; Jian-weng Gao; Zhenliang Wang; Yong-wen Cai; Shi-xin Tang (China Geology)
ABSTRACT: To understand the levels of potentially toxic elements (PTEs) contamination in soils and their effects on human health from different agricultural land use in Sanya, China. 128 soil samples (64 topsoil samples and corresponding subsoil samples) were collected from the five representative land-use patterns. Inductively coupled plasma mass spectrometry (ICP-MS), Atomic fluorescence spectrometry (AFS), and Inductively coupled plasma optical emission spectrometry (ICP-OES) were used to determine the content of PTEs (As, Cd, Hg, Cu, Cr, Ni, Pb, Zn, Co, Mo, Sb, and V). Correlation analysis and factor analysis were used to determine the source of PTEs. Geo-accumulation index (Igeo), hazard quotient (HQ), and total carcinogenic risk index (TR) were used to measure the PTEs contamination and its relative health impacts. Results showed that the average values of 12 PTEs in topsoil were higher than the Hainan soil geochemical baseline, showing different degrees of PTEs accumulation effect. The concentration of PTEs in the topsoil was lower than those in the subsoil except for Cd and Hg. The Igeo revealed that the major accumulated element in soils was As followed by Mo. Source apportionment suggested that parent materials and agricultural practices were the dominant factors for PTEs accumulation in the topsoil. Non-carcinogenic risks of soil samples from five land-use patterns presented a trend of paddy field > dry field > woodland > orchard > garden plot. However, the HQ values of 12 PTEs were less than the recommended limit of HQ = 1, representing that there are no non-carcinogenic risks of PTEs for children and adults in the study area. The TR values are within 6.95×10–6–1.38×10–5, which corresponds to the low level. Therefore the PTEs in the agricultural soil of the study area show little influence on the health status of the local population.